A Comparative Study of the Effectiveness of Video and Pocket Book to Improve the Couples’ Knowledge of Reproductive Health - Yatim, Darmayanti; Murni, Hasrah; Supiyah, Supiyah (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: The implementation of the sexual and reproductive health KIE program for prospective brides and groom in Bukittinggi has not been carried out according to standards due to various obstacles both from the input, process and output aspects. The most fundamental aspect is the absence of a local government-level policy that serves as a reference for implementing personnel to run this program. The results of research on the Analysis of the Implementation of Sexual and Reproductive Health KIE to prospective brides and groom in Bukittinggi, found that the media used were flip sheets and leaflets.Purpose: The purpose of the study was to determine the effectiveness of using video media and pocketbooks on the knowledge and attitudes of prospective brides and grooms.Methods: This is a quantitative with a Quasi-Experimental Two-Group pre-test-posttest research design, at 2 (two) health centers and Religious Affairs Offices (KUA) in 2 (two) Districts in Bukittinggi. Sampling was carried out by cluster sampling with the number of samples for groups using pocket book media and groups using video media. There were 30 samples for each media.  The instrument used was a questionnaire.  The analysis used Paired sample t-Test test n Gain score.Results: The results showed a significant difference in knowledge before and after intervention with pocket book and video media, p=0.00. The results of the N Gain Score test obtained the average value of pocket book learning media (66.46%) is greater than the average video media (58.14%), meaning that the use of learning media with pocket books is more effective and good for changing the level of knowledge of prospective brides and groom about sexual and reproductive health material.